Innovative Educational Scenarios in Game Based Teaching and Learning - Ion Smeureanu; Narcisa Isaila (Amfiteatru Economic Journal, 2017)
The didactical game can be considered part of an educational scenario in teaching and learning. This article aims to show how fundamental concepts from the economic - mathematical modeling area can be visualized, how to organize knowledge in coherent scenarios, presented in an educational game manner, to gain the attention and influence students' spirit of competition. At the same time, benefitting from the 3D visualizations, the graphical interfaces for navigating in multidimensional spaces or projections are defined and thus imagination used for mental models construction is stimulated and human intuition is capitalized in the process of knowledge discovery, assisted by computer with analytic algorithms type. Exploration becomes a game feature and can be pursued both numerically and visually. 3D environments give realism to visualizations that are found in games, facilitating realimaginary relationship throughout the game and enhancing learning motivation. The innovative character of teaching is given by the method in which the teacher creates his own educational scenario by considering specific learning objectives, age particularities of students, time and space-related resources, the technical requirements of the game and the evaluation method. The paper makes several references to such projects, developed by the authors and implemented in working with students. Game based on demonstration (using simulation, modelling or visualization) coordinates users to obtain relevant information; the multiple representations of knowledge are so used and compared through a multitude of examples.
Keywords: A2; A1; 330; educational game; teaching innovative; business game; 3D visualization; computer assisted